Energy Audit and Energy Consumption Analysis of the Campus Building Operation of the State Polytechnic of Samarinda - Halim, Abdul; Yusoff, Mohd Nazaruddin; Ali, Sharif Shofirun Sharif (Engineering, Technology & Applied Science Research, 2025)
Energy audits are essential for identifying the consumption patterns and enhancing the energy efficiency in buildings. This study investigates the energy use in two conventionally constructed buildings at the State Polytechnic of Samarinda: The Office of the Electrical Engineering Department (OEED) and the Office of the Mechanical Engineering Department (OMED). The key variables analyzed include temperature, relative humidity, Overall Thermal Transfer Value (OTTV), Roof Thermal Transfer Value (RTTV), and Energy Consumption Intensity (ECI) for both air-conditioned and non-air-conditioned spaces. In 2023, the average temperature and Relative Humidity (RH) were 28.8°C and 70.3% in OEED, and 28.4°C and 70.1% in OMED, respectively. The OTTV values were 61.51 W/m² (OEED) and 63.60 W/m² (OMED). ECI rose from 5.98 to 6.23 kWh/m²/month in OEED and from 4.57 to 4.85 kWh/m²/month in OMED between 2022 and 2023, yet remained within efficient benchmarks. However, the thermal comfort levels still necessitate air conditioning. The findings underscore the importance of implementing further efficiency measures to reduce the energy waste and improve sustainability on campus.